Criminal Responsibility for the Crime of Discharging Polluting Substances for Water Sources in Jordanian Legislation - ALMANASRA, Majd; ALKHSEILAT, Abdullah; AL-BILLEH, Tareq; ALWERIKAT, Naji; ALSHARQAWI, Ahmad Hussein (Journal of Environmental Management and Tourism; Vol 13 No 7 (2022): JEMT, Volume XIII, Issue 7(63), Winter 2022DO - 10.14505/jemt.v13.7(63).15, 2022)
This research seeks to clarify the conditions of Criminal Responsibility for the Crime of Discharging Polluting Substances for Water Sources, as the research's dilemma is the lack of effective penal provisions that prevent the offender from committing the crime of discharging polluting substances for water sources. Several conclusions and recommendations have been reached as a consequence of this research, the most important of which is the need for Jordan's criminal legislator to establish deterrent legal provisions that lead to not committing the crime of discharging polluting substances for water sources so that as countries around the world strive to preserve the territorial waters from any environmental pollution, these countries imposed a penalty on those who pollute the regional waters in any way.